ANALISIS PENGARUH PENEGAKAN HUKUM TERHADAP PERKEMBANGAN CYBER CRIME - Humala Simangunsong (Jurnal Mantik Penusa, 2018)
1992 on Film, Law Number 36 Year 1999 on Telecommunication, Article 5 Paragraph 1 and Article 13 Paragraph (1) Sub- Paragraph a of Law Number 40 Year 1999 concerning the Press, Article 36 Paragraph (5) of Law Number 32 Year 2002 on Broadcasting, Law Number 11 Year 2008 regarding Information and Transactions Electronic (UU ITE) and Law Number 44 Year 2008 regarding Pornography. The regulation is deemed inadequate when it is associated with the development of the Maya World Crime such as pornography on the internet now, its intercession is an unclear provision of pornography, the authorities to take certain actions in dealing with pornographic issues, the threat of too mild punishment, to account for crimes categorized as pornography, and inconsistent law enforcement.